A creator's guide to transmedia storytelling how to captivate and engage audiences across multiple platforms - Phillips, Andrea 1974- (McGraw-Hill, 2012)
This is the first major, comprehensive resource to feature concrete instruction on the principles of storytelling, audience engagement, platform selection, execution challenges, big-picture strategy and structural considerations -- as well as case studies of milestone transmedia projects and interviews with leading transmedia authorities and creators. Whether you're in game design and development, book publishing, film and television, or any other traditional or digital medium, A Creator's Guide to Transmedia Storytelling will give you the tools and knowledge you need to create deeper forms of audience engagement.